Handbook for liturgical studies - Chupungco, Anscar J. (Collegeville, Minn : Liturgical Press, 1997)
Contents: v.1 Introduction to the liturgy. v.2 Fundamental theology. v.3 The Eucharist. v.4 Sacraments and sacramentals. v. 5 Liturgical time and space
" A Pueblo Book " Includes bibliographical references and indexes
Keywords: Liturgics -- Study and teaching; Catholic Church -- Liturgy -- Study and teaching